Hydrodynamic numerical modelling of the water level decline in four temporary ponds of the Doñana National Park (SW Spain). (December 2017) - Dimitriou, Elias; Moussoulis, Elias; Díaz-Paniagua, Carmen; Serrano, Laura
Abstract: Water level changes have been monitored over 25 years in several temporary ponds located at different distances to a pumping area of a tourist resort fringing the Doñana National Park (SW Spain). The numerical model MIKE SHE was set up to simulate pond water levels and hydroperiod fluctuations. It was calibrated for nine hydrological years and validated for two periods of eight hydrological years each to assess whether the duration of the pond wet phase (hydroperiod) significantly deviated from an expected pattern driven by rainfall and evapotranspiration. The model output indicated a satisfactory performance for all simulations. This approach provided two main conclusions: a) a long-term increasing trend in water losses on the pond water balance which has not been followed by a corresponding decreasing trend in rainfall, and b) these water losses were highest in the pond located at < 1 km to the pumping area and lowest in the pond located at a further distance (5.6 km) and at a lower altitude. Our results suggest that, in the long run, a small groundwater abstraction rate has exerted a high hydrological pressure on the closest pond to the pumping area. Highlights: Hydrological impacts simulation in priority habitats using dynamic modelling. Estimation of water losses in Temporary Ponds by using water balance approaches. Anthropogenic pressures on temporary ponds can overcome impacts from natural factors.